Penyelesaian Perkara Tindak Pidana Pencemaran Limbah B3 dengan Menggunakan Pendekatan Restorative Justice - M Lubis, Hanna Patricia; Sari Hariyanto, Diah Ratna (Kertha Negara : Journal Ilmu Hukum, 2024)
This study aims to determine whether Environmental Law cases can be resolved using a Restorative Justice approach. Also, using a restorative approach to find out the legal consequences and impacts of settlements. The Restorative Justice Approach is an approach that leads to the creation of justice and balance for the perpetrators of the crime and the victim. This study uses a normative juridical approach. The method of collecting legal materials in this research is library research. The results of the study show that Restorative Justice can be fairer because in court, mediation is carried out between the people of Metro (as victims) over B3 waste pollution by PT Sutomo (as perpetrators), and the legal consequences in the settlement are in the form of stopping investigations from avoiding criminal sanctions and reducing the accumulation of cases through the discretion of law enforcement in fulfilling the material and formal requirements stipulated in the Chief of Police Circular Number: SE/8/VII/2018.